IMPROVING STUDENTS’ SPEAKING SKILL BY USING VIDEO IN EXPRESSSING IDENTITY TO THE FIFTH GRADE STUDENTS OF SDN 032 TAMBUSAI UTARA - Nurazima Juhastri, Azi; Rahayu, Pipit; Eripuddin; Permata Sari, Intan (JEE (Journal of English Education), 2024)
This research was purposed to improve students’ speaking skill in expressing identity to the grade 5 students in SDN 032 Tambusai Utara. The researcher chose the students from class 5 to be the object of this research. This research was designed as a Classroom Action Research (CAR) which was purposed to improve students’ speaking skill in expressing identity through video technique. In this research, there were 17 students of class 5 as the object of the research. The researcher used 2 cycles in collecting the data of the research where every cycle consists of 3 meetings. In the first meeting of cycle 1 the students’ average score was 34,11 classified as very poor level. In the second meeting of cycle 1 students’ average score was 42,64 and it was very poor level. In the third meeting of cycle 1, students average score was 54,35 and it was very poor level. In the second cycle, teacher tried to do the same activities to improve students’ speaking skill. In the first meeting of cycle 2 the students’ average score was 57,64 classified as very poor level. In the second meeting of cycle 2 students’ average score was 61,47 and it was poor level. In the third meeting of cycle 2, students average score was 65,29 and it was in the fair level. From the findings above it can be concluded that the use of video technique can improve students’ speaking skill in expressing identity.